AKIBAT HUKUM PENGGUNAAN DANA REFRESENTATIF YANG TIDAK DIPERTANGGUNGJAWABKAN OLEH DIREKSI PDAM - MARIAH SONANGGOK M. PURBA (JURNAL ILMIAH MAKSITEK, 2018)
Representative funds are funds received by the director of PDAM at the most 75% (seventy five percent) of the amount income of directors in a year, that used to support the further of PDAM management. The basis law receiving of representative fund is pharagraph 10Permendagri No. 2/2007 about the Organs and employee drinking water area company. Hope having a rule coming a justice, certainty of law, and utilization arround of society.But it’s not seldom happened, the rule that written unclear, or it’s not clear to set about something. Pharagraph 10 Permendagri No. 2/2007 is one of the rule that setting about represenative fund. But the rule is not clear for use right now. And the effect for doesn’t use that funds aecording to the application and it is not responsibility involved happen a dissarantage of country